2017
DOI: 10.3390/ijms18040740
|View full text |Cite
|
Sign up to set email alerts
|

Cancer/Testis Antigens: “Smart” Biomarkers for Diagnosis and Prognosis of Prostate and Other Cancers

Abstract: A clinical dilemma in the management of prostate cancer (PCa) is to distinguish men with aggressive disease who need definitive treatment from men who may not require immediate intervention. Accurate prediction of disease behavior is critical because radical treatment is associated with high morbidity. Here, we highlight the cancer/testis antigens (CTAs) as potential PCa biomarkers. The CTAs are a group of proteins that are typically restricted to the testis in the normal adult but are aberrantly expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 152 publications
(206 reference statements)
1
20
0
1
Order By: Relevance
“…Cancer testis antigens (CTAs) have been extensively studied in a variety of cancers of diverse histological origin and germinal cells (Lim et al, 2012;Zajac et al, 2017). However, the majority of these studies focused on the correlative expression data and/or on evaluating their immunotherapeutic targeting or tumor biomarker values, with limited studies on their gene expression regulation and even fewer on their cellular function in cancer cells (Lim et al, 2012;Kulkarni and Uversky, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer testis antigens (CTAs) have been extensively studied in a variety of cancers of diverse histological origin and germinal cells (Lim et al, 2012;Zajac et al, 2017). However, the majority of these studies focused on the correlative expression data and/or on evaluating their immunotherapeutic targeting or tumor biomarker values, with limited studies on their gene expression regulation and even fewer on their cellular function in cancer cells (Lim et al, 2012;Kulkarni and Uversky, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The procedure of germ cell formation and tumorigenesis has significant similarities, involving cell immortalization, migration and invasion, induction of meiosis . CT genes have been known as prospective cancer markers and objectives for therapy . The activation of CT gene expression in various types of tumours was observed .…”
Section: Discussionmentioning
confidence: 99%
“…7 CT genes have been known as prospective cancer markers and objectives for therapy. 20 The activation of CT gene expression in various types of tumours was observed. 21,22 Previous study found that the activation frequency of CT gene is much changeful depending on cancer type, the melanomas, the liver and lung cancers could show a high rate of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…CTAs by definition are normally expressed in testis and other developmentally regulated tissues (e.g., placenta) but are aberrantly expressed in many types of cancers [19]. This unique pattern of expression makes these genes attractive candidates as biomarkers and, together with their immunogenic capacity, also good targets for the development of cancer immunotherapy [20][21][22]. The aberrant expression of CTAs in different cancer types is associated with phenotypic changes that confer cancer cells added advantages for proliferation and survival [23,24].…”
Section: Introductionmentioning
confidence: 99%